144 Rumen Fluid Metabolites as Potential Biomarkers of Feed Efficiency in Angus Steers. (28th November 2020) - Clemmons, Brooke A; Powers, Joshua B; Campagna, Shawn R; Ault, Taylor B; Embree, Mallory M; Myer, Phillip R
Abstract: Beef cattle is the most consumed red meat in the United States, and the United States is the largest producer and consumer of beef cattle globally. Feed is one of the largest input costs for the beef cattle industry, accounting for 40–60% of the total input costs. Identifying methods for improving feed efficiency in beef cattle herds could result in decreased cost to both producers and consumers, as well as increased animal protein available for global consumption. Identification of feed efficiency biomarkers could aid in the selection of more feed-efficient animals. To identify potential biomarkers of feed efficiency, rumen fluid was collected from low- (n = 14) and high-RFI (n = 15) Angus steers based on RFI ± 0.5 SD around the mean following a 70d feed efficiency trial to determine rumen metabolites associated with variations in feed efficiency. Steers were 7 months of age, weighing 264±2.7 kg. Rumen fluid was collected via gastric tubing, filtered through a 0.22 µM syringe filter, extracted for metabolomic analysis using 0.1% formic acid in acetonitrile:water:methanol (2:2:1), and injected into the Dionex UltiMate 3000 UHPLC system with an Exactive Plus Orbitrap MS. Peaks for known metabolites were identified using MAVEN and analyzed using MetaboAnalyst 4.0 and SAS. Significance was determined using an α ≤ 0.05. Based on fold change (high/low RFI), eight metabolites were greater in low-RFI steers compared to high-RFI steers, including 3, 4-dihydroxyphenylacetate, 4-pyridoxate, citraconate, hypoxanthine, succinate/methylmalonate, thymine, uracil, and xylose (P ≤ 0.05), while 12 metabolites differed by ≥ 2-fold. These metabolites were predominantly involved in amino acid and lipid metabolism. Rumen fluid metabolomes differed in steers of varying feed efficiencies. These metabolites may be used as biomarkers of feed efficiency and may provide insight as to factors contributing to differences in feed efficiency that may be exploited to improve feed efficiency in beef cattle herds.